Assessing the Impact of the “Empowering the Coastal Community” Extension Program During the COVID-19 Pandemic - Tabanao, Eden Grace; Buenaflor, Jing; Delgado, Ramon (Journal of Interdisciplinary Perspectives, 2025)
Abstract. This study assessed the impact of the “Empowering the Coastal Community” Extension Program implemented in Barangay Malusay, Guihulngan City, Negros Oriental, Philippines, during the COVID-19 pandemic. The program sought to enhance the community’s knowledge, skills, and values related to health, sanitation, vaccination, and environmental management amid the challenges brought by the health crisis. While many extension programs have been implemented across local communities, few studies have examined their actual effectiveness in fostering community empowerment and sustainable development during times of crisis. To address this gap, the study employed a descriptive research design utilizing an adapted and validated questionnaire to determine the extent of the program’s impact. A total of 60 purposively selected respondents, composed of barangay officials, barangay health workers, and Pantawid beneficiaries who also received the extension program, participated in the study. The data were analyzed using frequency, percentage, and weighted mean to interpret the results. Findings revealed that the respondents demonstrated a high level of acquired knowledge (overall weighted mean = 2.70, Strongly Agree), particularly in COVID-19 prevention, vaccination awareness, and hygiene and sanitation practices. Likewise, they exhibited strong skills (overall weighted mean = 2.58, Strongly Agree) in applying health and safety measures, waste management, and urban gardening, although the latter was rated slightly lower. The program also significantly influenced values and attitudes (overall weighted mean = 2.63, Strongly Agree), highlighting a deeper appreciation for public health, a sense of responsibility for community hygiene, and commitment to environmental protection. Overall, the study concludes that the extension program effectively strengthened community awareness, improved health practices, and fostered ecological stewardship. These outcomes demonstrate the vital role of university-led extension programs in promoting community empowerment and sustainable development, aligning with Sustainable Development Goals (SDGs) 3, 4, 11, and 13.